Vocational Higher Education and Training in Brazil and the Quality Control - Zapparoli, Irene Domenes; Zapparoli, Ferdinando Vinicius Domenes (Olhar de Professor, 2009)
This research focuses the sequential courses, a way of vocational higher education introduced in Brazil in 1999. The aim of this study is to show a general overview on vocational education in Brazil, the development of sequential courses, about the Brazilian universities and the representative institutions of category (syndicates, regional counseling, federations and confederations) and the quality control. These courses, with two years lasting, were implemented to develop in the students older than sixteen the professional background. These sequential courses are in the beginning phases of implementation, so there are not researches about them yet. However, the interest in sequential courses is increasing since they were implemented. Data from Ministry of Education point that in 1999 were offered one hundred seventy-eight courses in Brazil, meantime in 2002 the offering was six hundred twelve courses. Although the data show the sequential courses have been well accepted by Brazilian students, it is not possible to notice, if they fulfill the students expectations. The methodology to this work was developed through a bibliographic review about vocational education. Beyond the students, this research considers other important institutions or involved elements with this pattern of education and sequential courses, among them the government, the representative counseling of category, the teachers and the universities. We observed that there are many relevant questions those deserve some reflection related to different parts of these courses such as: a) the lack of links between the Ministry of Education and the Ministry of Labour, which leads to problems of recognition of the sequential courses in the labour market; b) the different points of view of trade unions, with some against and others in favour of this new kind of training workforce in Brazil; and c) the controversy among universities whether it is their role to offer sequential courses in addition to regular undergraduate degrees, partly because of their concerns regarding the quality of these courses. Key words: vocational education - sequential courses - workforce.